1995
DOI: 10.1111/j.1365-2133.1995.tb02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratoderma with scleroatrophy of the extremities or sclerotylosis (Huriez syndrome): a reappraisal

Abstract: Keratoderma with scleroatrophy of the extremities, also referred to as Huriez syndrome, is a rare, autosomal dominant condition, first described in 42 of 132 members of two families from northern France. The term sclerotylosis was proposed because of the pseudosclerodermatous appearance of the hands and digits. The distinctive feature of this syndrome is the risk of the development of squamous cell carcinoma on affected skin. Since the initial description of this disease, three other families, and possibly a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
6

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 17 publications
1
21
0
6
Order By: Relevance
“…Deminatti et al [16] reported a linkage between Huriez syndrome and the MNS blood group, later mapped to chromosome 4 (4q28-31). However, subsequent studies failed to show any clear linkage for the disorder [5,8]. Recently, Lee et al [6] have performed a linkage analysis in members of one of the families first described by Huriez et al [2] and another family originating from the same region of northern France, and mapped the gene to chromosome 4q23.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Deminatti et al [16] reported a linkage between Huriez syndrome and the MNS blood group, later mapped to chromosome 4 (4q28-31). However, subsequent studies failed to show any clear linkage for the disorder [5,8]. Recently, Lee et al [6] have performed a linkage analysis in members of one of the families first described by Huriez et al [2] and another family originating from the same region of northern France, and mapped the gene to chromosome 4q23.…”
mentioning
confidence: 99%
“…The sites of SCC have been described in 13 cases of Huriez syndrome; 12 cases were on the hand (6 cases on the finger [1,2,5,8,15], 2 cases on thenar eminence [7,9] and the rest just on the 'hand') and 1 case on the heel [9]. SCC that develops in Huriez syndrome has been reported to be more aggressive than SCC in the general population.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, no reports have described the association of PLS with nonmelanoma skin carcinomas, such as squamous cell carcinoma, developing within the hyperkeratotic skin. In contrast, other types of PPK, such as Olmsted syndrome [25] and Huriez syndrome [26, 27], are reportedly associated with squamous cell carcinoma. In this context, mal de Meleda might also possess this preferential tendency of melanoma development; so far, no association of nonmelanoma skin cancers has been reported for this disease.…”
Section: Discussionmentioning
confidence: 99%